A biomechanical comparison between transosseous cruciate sutures and suture anchors for triceps tendon repair: a systematic review and meta-analysis. Issue 6 (30th November 2022) - Sequeira, Sean B.; Imbergamo, Casey; Gould, Heath; Wright, Melissa A.; Murthi, Anand M.
Abstract : Background: The most common surgical option for acute triceps tendon tears is primary repair. There is no consensus as to which fixation construct is biomechanically superior. The purpose of this study was to evaluate the biomechanical properties of transosseous cruciate (TC) versus suture anchors (SA) for triceps tendon repair. Methods: A systematic review was performed by searching PubMed, the Cochrane library, and Embase using Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines to identify studies that analyzed the biomechanical properties of TC and SA techniques for triceps tendon repair. The search phrase implemented was "triceps tendon repair biomechanics." Evaluated outcomes included medial displacement, lateral displacement, and ultimate load to failure. Results: Four studies met inclusion criteria, including 74 cadaveric specimens (TC: 37, SA: 37), for triceps tendon repair comparing a transosseous technique with TC to SA fixation. Pooled analysis from four studies reporting on medial and lateral displacement revealed a statistically significant difference between TC and SA ( P =0.048 and 0.006). Pooled analysis from three studies reporting on ultimate load to failure revealed a statistically significant difference in favor of SA compared to TC ( P =0.035). Conclusions: Biomechanical testing of SA for triceps tendon repair is associated with higher ultimate load to failure and lower medial and lateral displacement when under load following repair. The findings of this biomechanical meta-analyses should be considered along with clinical outcome data when surgeons make a decision regarding triceps tendon repair techniques. Level of Evidence: Level II